Observations on the Inhibitory Effect of Sodium Chloride on Molds met within Smoked Fishery Products - Appuraj, V. E.; A. P. Valsan (Fishery Technology, 1966)
Even though smoke curing is a very elegant method of preserving fish, the resultant products have only a very restricted shelf-life, unless stored under refrigerated conditions. The main source of spoilage is the early setting in of a vigorous growth of molds. This problem is of a serious nature even in temperate climatic conditions. In full and universal recognition of the gravity of the problem, the F. A. O. conference on Herring technology held in September 1950 at Bergen in Norway has recommended the problem of "means of prevention of mold growth in smoked products" for future research study. This note records an interesting observation made at this Laboratory ·on the inhibitory acti6n of sodium chloride on the development of molds in smoked fishery products. It was noted that the control sample without any salt sprinkling was affected by a vigorous growth of molds within the short period of 3-5 days and also developed an unpleasant off flavour. The product was completely unfit for consumption within the first week itself. However, the experimental sample with the sprinkling of sodium chloride was unaffected by molds and the above described general deteriorations, even after an extended storage period of 2 months. Smoke curing with sprinkling of sodium chloride is thus a simple, cheap and safe practice, making it more economical and practical under Indian conditions.